Reduced Intravoxel Incoherent Motion Microvascular Perfusion Predicts Delayed Cerebral Ischemia and Vasospasm After Aneurysm Rupture. Issue 3 (March 2018) - Heit, Jeremy J.; Wintermark, Max; Martin, Blake W.; Zhu, Guangming; Marks, Michael P.; Zaharchuk, Greg; Dodd, Robert L.; Do, Huy M.; Steinberg, Gary K.; Lansberg, Maarten G.; Albers, Gregory W.; Federau, Christian
Abstract : Background and Purpose—: Proximal artery vasospasm and delayed cerebral ischemia (DCI) after cerebral aneurysm rupture result in reduced cerebral perfusion and microperfusion and significant morbidity and mortality. Intravoxel incoherent motion (IVIM) magnetic resonance imaging extracts microvascular perfusion information from a multi-b value diffusion-weighted sequence. We determined whether decreased IVIM perfusion may identify patients with proximal artery vasospasm and DCI. Methods—: We performed a pilot retrospective cohort study of patients with ruptured cerebral aneurysms. Consecutive patients who underwent a brain magnetic resonance imaging with IVIM after ruptured aneurysm treatment were included. Patient demographic, treatment, imaging, and outcome data were determined by electronic medical record review. Primary outcome was DCI development with proximal artery vasospasm that required endovascular treatment. Secondary outcomes included mortality and clinical outcomes at 6 months. Results—: Sixteen patients (11 females, 69%; P =0.9) were included. There were no differences in age, neurological status, or comorbidities between patients who subsequently underwent endovascular treatment of DCI (10 patients; DCI+ group) and those who did not (6 patients; DCI− group). Compared with DCI− patients, DCI+ patients had decreased IVIM perfusion fraction f (0.09±0.03 versus 0.13±0.01; P =0.03), reduced diffusion coefficient D (0.82±0.05 versus 0.92±0.07×10 −3 mm 2 /s; P =0.003), and reduced blood flow–related parameter fD * (1.18±0.40 versus 1.83±0.40×10 −3 mm 2 /s; P =0.009). IVIM pseudodiffusion coefficient D * did not differ between DCI− (0.011±0.002) and DCI+ (0.013±0.005 mm 2 /s; P =0.4) patients. No differences in mortality or clinical outcome were identified. Conclusions—: Decreased IVIM perfusion fraction f and blood flow–related parameter fD * correlate with DCI and proximal artery vasospasm development after cerebral aneurysm rupture. Abstract : Supplemental Digital Content is available in the text.